2017
DOI: 10.1371/journal.pone.0171646
|View full text |Cite
|
Sign up to set email alerts
|

Selection and evaluation of new reference genes for RT-qPCR analysis in Epinephelus akaara based on transcriptome data

Abstract: Groupers are an economically important fish species in world fishery markets. Because many studies using RT-qPCR have addressed gene expression in groupers, appropriate reference genes are required to obtain reliable and accurate results. In this study, the most suitable reference genes were identified from eleven candidate genes of one of the most valuable species, Epinephelus akaara, in a range of different experimental conditions. Using the software packages geNorm, NormFinder, BestKeeper and refFinder, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
(65 reference statements)
2
18
1
Order By: Relevance
“…Also, when we compared the distribution of comprehensive rankings of the gene groups, the novel candidates genes in the group 2 were constantly more stable than the other two groups ( Fig 5 ), indicating that traditionally used reference genes are often not the best choice for the normalization of RT-qPCR data in mosses under conditions of abiotic stress. The usefulness of transcriptome data for identifying robust normalizers is consistent with previous reports on the validation of novel reference genes based on transcriptome data [ 39 , 40 ]. However, it is still necessary to validate the gene reliability individually even after the candidate gene selection from transcriptome data.…”
Section: Discussionsupporting
confidence: 87%
“…Also, when we compared the distribution of comprehensive rankings of the gene groups, the novel candidates genes in the group 2 were constantly more stable than the other two groups ( Fig 5 ), indicating that traditionally used reference genes are often not the best choice for the normalization of RT-qPCR data in mosses under conditions of abiotic stress. The usefulness of transcriptome data for identifying robust normalizers is consistent with previous reports on the validation of novel reference genes based on transcriptome data [ 39 , 40 ]. However, it is still necessary to validate the gene reliability individually even after the candidate gene selection from transcriptome data.…”
Section: Discussionsupporting
confidence: 87%
“…The calculated copy number of the samples was presented relative to that of the reference gene (conserved oligomeric Golgi complex subunit 5, Cog5). Cog5 was chosen as the reference gene for this study as recommended from a previous study [32] showing its stable expression in gonadal tissue of another grouper species, E. akaara.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…In our study, EF1α was found to be the most stable gene in all the healthy tissues, whereas GAPDH was ranked as the least stable gene by all the four methods. The concurrent finding has also been observed for the gene expression profile of Epinephelus akaara, wherein GAPDH and actin-β were the least stable genes (Wang et al 2017). Paria et al (2016) reported that EF1α and actin-β as the most stably expressed transcripts in the normal tissues of Asian seabass.…”
Section: Discussionmentioning
confidence: 62%
“…The expression of housekeeping genes varies with various factors such as development, stress, and infection, and a thorough validation of housekeeping genes for different factorial conditions is desirable (Bustin 2000). Studies on reference gene validation have been undertaken in various fish species for different experimental conditions (Olsvik et al 2005;Fernandes et al 2008;Tang et al 2007;Zheng and Sun 2011;Purohit et al, 2016;Paria et al 2016;Wang et al 2017). In our study, EF1α was found to be the most stable gene in all the healthy tissues, whereas GAPDH was ranked as the least stable gene by all the four methods.…”
Section: Discussionmentioning
confidence: 99%